Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Ca Paru Di Ruang Inap Paru RSUP Dr. M. Djamil Padang - Nilam Zulaikha; Mike Asmaria; Aulia Asman; Kheniva Diah Anggita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Based on IARC data, Lung Cancer is the leading cause of death in the world, almost 2.5 million people were diagnosed with Lung Cancer and more than 1.8 million people died. In Indonesia, there were 30,843 cases of Lung Cancer and 26,069 deaths due to this disease. In West Sumatra, Lung Cancer cases reached 150 cases in 2022. At Dr. M. Djamil Padang General Hospital, 288 cases of Lung Cancer were recorded in 2025, therefore serious treatment is needed for this Lung Cancer case. The purpose of this study describes the implementation of nursing care for Lung Cancer patients using a case study method where researchers took 1 patient to apply nursing care. The study was conducted on February 4-9. The results of the study obtained complaints such as coughing up phlegm, shortness of breath, prolonged expiratory phase, Hb 10.3, pain in the left chest, the patient had no appetite, the patient was tired, and there was a WSD insertion wound. Nursing problems established were ineffective airway clearance, ineffective breathing pattern, ineffective peripheral perfusion, acute pain, nutritional deficit, activity intolerance, risk of infection. Interventions provided were airway management, effective coughing exercises, ventilation support, circulation care, blood transfusion, pain management, nutrition management, energy management, infection prevention. Evaluation of ineffective airway clearance, nutritional deficit, activity intolerance resolved on the sixth day, ineffective breathing pattern, acute pain, ineffective peripheral perfusion resolved on the fifth day, risk of infection on the fourth day. It was concluded that comprehensive and continuous nursing care was effective in improving the condition of Lung Cancer patients. It is recommended to undergo regular treatment, implement a healthy lifestyle, and conduct regular health checks.